2012
DOI: 10.1002/ejic.201200616
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Arylene and Alkylene Units on the Structuring of Urea‐Based Bridged Silsesquioxanes

Abstract: The influence of the intrinsic self-assembling properties of rigid or semirigid aromatic units as the main substructures combined with the effect of the alkylene side chains as linkers on the nanostructure of bridged silsesquioxanes was studied. The symmetry of the organic units was found to control the dimensionality of the hybrid nanostructure. Bis(silyl-Eur. Synthesis of the Molecular Precursors P1-6 and the Corresponding Hybrid Bridged Silsesquioxanes HS1-6Bis(silylated) molecular precursors P1-4 were synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Such systems include disulfide‐ and tetrasulfide‐doped PMO NPs (for glutathione‐mediated biodegradation in cells), and degradable oxamide‐ or lysine‐doped PMO NPs. Fourth, solid nonporous BS NPs can also be constructed from bridged multi‐organoalkoxysilanes (Figure D) . The absence of specific interactions between micelles and bridged organoalkoxysilanes produces dense NPs with high organic content in the composite matrix …”
Section: Two‐photon‐sensitive Organosilica Nanomaterialsmentioning
confidence: 99%
“…Such systems include disulfide‐ and tetrasulfide‐doped PMO NPs (for glutathione‐mediated biodegradation in cells), and degradable oxamide‐ or lysine‐doped PMO NPs. Fourth, solid nonporous BS NPs can also be constructed from bridged multi‐organoalkoxysilanes (Figure D) . The absence of specific interactions between micelles and bridged organoalkoxysilanes produces dense NPs with high organic content in the composite matrix …”
Section: Two‐photon‐sensitive Organosilica Nanomaterialsmentioning
confidence: 99%
“…50,51 Bromoundecene (Alpha Aesar) was rst mixed with triethoxysilane and Karstedt catalyst both purchased from ABCR to obtain bromoundecyl-triethoxysilane. 50,51 Bromoundecene (Alpha Aesar) was rst mixed with triethoxysilane and Karstedt catalyst both purchased from ABCR to obtain bromoundecyl-triethoxysilane.…”
Section: Synthesis Of Amino-undecyl-triethoxysilanementioning
confidence: 99%
“…Other diureido derivatives including aryl groups91 to provide additional aromatic π–π stacking interactions ( 10 , Figure 14) or diaminocyclohexane92 to introduce chirality effects ( 11 , Figure 14) turned out to be effective building blocks for the synthesis of highly ordered self‐organized hybrid solids. The authors also focused on the influence of the experimental conditions,93 the alkylene chain length,94 and arylene structure95 on the mesostructuration process. They showed that pH affects not only hydrolysis/polycondensation kinetics, but also hydrogen‐bonding‐driven structuration when pH‐sensitive functions, such as carbamate groups, are involved.…”
Section: Self‐assembly Of Bis‐silylated Organosilanesmentioning
confidence: 99%